DESCRIÃ‡ÃƒO DE NOVA ESPÃ‰CIE DE ð˜Šð˜°ð˜³ð˜ºð˜»ð˜°ð˜±ð˜ð˜¢ð˜µð˜¶ð˜´ (ð˜ð˜¦ð˜®ð˜ªð˜±ð˜µð˜¦ð˜³ð˜¢-ð˜Šð˜°ð˜³ð˜¦ð˜ªð˜¥ð˜¢ð˜¦) - Mariconi, Francisco A. M. (REVISTA DE AGRICULTURA, 2020)
DESCRIÃ‡ÃƒO DE NOVA ESPÃ‰CIE DE ð˜Šð˜°ð˜³ð˜ºð˜»ð˜°ð˜±ð˜ð˜¢ð˜µð˜¶ð˜´ (ð˜ð˜¦ð˜®ð˜ªð˜±ð˜µð˜¦ð˜³ð˜¢-ð˜Šð˜°ð˜³ð˜¦ð˜ªð˜¥ð˜¢ð˜¦)